Integration of Environmental Education and Moral Education within the Adiwiyata Program in Madrasahs (Journal Of Islamic Education And Pesantren, 2025)
This study aims to analyze the integration of environmental education and moral education in the implementation of the Adiwiyata Program in madrasahs as an effort to develop students’ Islamic character with ecological awareness. The study employed a qualitative approach using a case study design conducted at MTs Madrasatul Qur’an. Data were collected through observation, in-depth interviews, and documentation involving the madrasah principal, teachers, and students. Data analysis was carried out through the stages of data reduction, data display, and conclusion drawing, with data trustworthiness ensured through source and technique triangulation. The findings indicate that the integration of environmental education and moral education within the Adiwiyata Program is implemented in a systemic and sustainable manner through the alignment of environmentally oriented madrasah policies, contextual curriculum development integrated with Islamic moral values, participatory environmental activities, the management of environmentally friendly facilities and infrastructure, and habituation embedded in the madrasah culture. Environmental education functions as a strategic practical and pedagogical medium that enables the internalization of Islamic moral values—such as trustworthiness (amanah), responsibility, discipline, and care—through direct experience and continuous habituation in students’ daily lives. This study concludes that the Adiwiyata Program holds strategic potential as a model for strengthening Islamic moral education based on environmental awareness in madrasahs.